Sports participation plays a relevant role in the relationship between birth weight and bone mineral content in adolescents - Urban, Jacqueline Bexiga [UNESP] (2024)
The Developmental Origins of Health and Disease hypothesis (DOHaD) proposes that growth during the prenatal period might play a critical role in health, affecting the development of diseases, such as osteoporosis. Bone health is particularly affected by human behaviors when sports participation constitutes the main manifestation of physical exercise. The aim of this study is to analyze the relationship between birth weight (BW) and bone mineral content (BMC) among adolescents, as well as to identify if sports participation and maturity can affect this relationship. The sample was composed of adolescents with ages ranging from 11 to 18 years, stratified according to normal birth weight (n = 331), low birth weight (n = 36), and macrosomia (n = 47), extracted from a wider cross-sectional study (ABCD Growth Study). BW was self-reported by the adolescent's parent. Sports participation was assessed by face-to-face interview. BMC was assessed using dual-energy X-ray absorptiometry. In the multivariate models, the relationships between BW and BMC remained non-significant, while sports participation was significantly related to BMC on lower limbs among boys (r = 0.154; p value =.001) and BMC of upper limbs among girls (r = 0.124; p value =.044). APHV was related to BMC of upper limbs among boys (r = 0.137; p value =.001). In conclusion, BMC was not affected by BW, while this phenomenon seems to be significantly affected by the positive impact of sports participation and maturation on it.